INDUSTRIAL NETWORKS OF THE REGION INNOVATIVE APPROACH TO DEVELOPMENT (Ta'limning zamonaviy transformatsiyasi, 2024)
In the conditions of the globalization of the world economy, to cope with the competition in the industrial enterprises of the regions, aimed at modern advanced technologies and innovations use, activities of economic entities and increasing efficiency is important. In the world comprehensive development of industrial enterprises, innovative to them export of products due to the wide introduction of developments geographical expansion and sustainable economic development determine the main priorities. "Industry in the gross domestic product (GDP) of developed countries." an average of 40% of the share»9 coming right, developing This network is expected to be on average 20-25% in the countries requires development.В условиях глобализации мировой экономики, чтобы выдержать конкуренцию на промышленных предприятиях регионов, нацелен на современные передовые технологии и инновации использование, деятельность хозяйствующих субъектов и важно повысить эффективность. в мире комплексное развитие промышленных предприятий, их инновационность экспорт продукции за счет широкого внедрения продукции географическое расширение и стабильное экономическое развитие Достижение высоких скоростей определяет главное устойчивость. «Валовой внутренний продукт (ВВП) развитых стран – это промышленность в среднем 40% акций»9 идет правильно, развивается В будущем эта сеть увеличится в среднем на 20-25% по странам. требует развития.